Thermal and compositional driven relaxor ferroelectric behaviours of lead-free Bi0.5Na0.5TiO3–SrTiO3 ceramics. Issue 7 (20th January 2020) - He, Hongying; Lu, Xin; Li, Minchan; Wang, Yumei; Li, Zhenrong; Lu, Zhouguang; Lu, Li
Abstract : The dielectric, piezoelectric and ferroelectric properties of (1 − x )(Bi0.5 Na0.5 )TiO3 – x SrTiO3 ceramics are systematically studied to investigate their relaxor ferroelectric behaviours driven by thermal and compositional changes. Abstract : The dielectric, piezoelectric and ferroelectric properties of (1 − x )(Bi0.5 Na0.5 )TiO3 – x SrTiO3 (BNT–ST) ceramics (0 ≤ x ≤ 0.30) are systematically studied in order to investigate their relaxor ferroelectric behaviours driven by thermal and compositional changes. The significant enhancement of the piezoelectric coefficient ( d 33 = 152 pC N −1 ) has been observed for x = 0.20. In addition, the BNT–24ST ceramic exhibits an electric field-induced strain of 0.20% at 7 kV mm −1 and a normalized strain d 33 * of 266 pm V −1 . The increase in the ST content drives BNT from the ferroelectric to relaxor ferroelectric state due to the rising disordering level. In addition, the behaviours of the field-induced metastable ferroelectric to relaxor phase transition are studied based on the anomalies in the temperature dependence of the dielectric properties. To investigate the thermal-induced domain behaviour, in situ piezoresponse force microscopy (PFM) is used to observe the domain structures of the poled BNT–16ST ceramic upon heating and cooling. This study provides evidence for understanding the relaxor ferroelectric behaviours of the BNT–ST ceramics.